The Impact of “CODE STEMI” Program Implementation on Door to Balloon Time and Major Adverse Cardiac Events of Patients with ST Elevation Myocardial Infarction - Funay, Prijander L B; Wijaya, Ika Prasetya; Ginanjar, Eka; Shatri, Hamzah (UI Scholars Hub, 2020)
Introduction. Delay in the management of ST Elevation Myocardial Infarction (STEMI) patients is a cause of high mortality and the incidence of major adverse cardiac events (MACE). Efforts that can be made in health facilities with primary percutaneous coronary intervention (PCI) capability are achieving timely reperfusion of STEMI patients. Various strategies were carried out to achieve timely reperfusion including implementation the CODE STEMI program. This study aimed to determine the effect of the implementation of the CODE STEMI program on Door to Balloon Time (D2BT) and MACE of STEMI patients undergoing primary PCI. Methods. This was a retrospective cohort study conducted among STEMI patients undergoing primary PCI before the application of the CODE STEMI program (2015-2016) and after the application of the CODE STEMI program (2017-2018). Data were obtained from patients’ medical record. Analysis was performed quantitatively by Mann Whitney test for D2BT and chi square for MACE. Results. There were 111 patients in the non-CODE STEMI group and 144 patients in the CODE STEMI group. D2BT decreased significantly 110 minutes from 275 (99-2356) minutes in the non-CODE STEMI group to 165 (67-1165) minutes in the CODE STEMI group (p < 0.001). Analysis in both group (CODE STEMI vs. non-CODE STEMI) showed as follows: MACE events (48.4% vs 51.6%; p = 0.120), heart failure (46.6% vs 42%; p = 0.288), cardiogenic shock (27% vs 19.4%; p = 0.152), arrhythmia (12.6% vs 6.2%; p = 0.079), stroke (4.5% vs 5.6%; p = 0.705), and mortality rate (7.2% vs 3.5%; p = 0.179) which were similar between the two groups. The incidence of reinfarction (4.5% vs 0.7%; p = 0.047) and repeated PCI (2.7% vs 0.0%; p = 0.047) were significantly reduced in the CODE STEMI group. Conclusions. The CODE STEMI program reduces D2BT. The CODE STEMI program did not reduce the overall MACE incidence but reduced the incidence of reinfarction and repeated PCI of STEMI patients undergoing primary PCI